Integrated farm and ubi powder production plant - Gonzales, Ana Liza V.; Olfindo, Pazette T.; Pacomo, Fiorella R.; Santos, Sherwin S. (Diliman, Quezon City College of Engineering, 1997)
CapacityL 163,000 kgs. ubi powder -- Plant location: Eastern Quezon -- Land area: 22 ha. -- Fixed capital investment:L Php 41,469,990 -- Annual production: 163,800 kgs. -- Total product cost at maximum production: Php 21,580,898 -- Annual sales at maximum production: Php 45,571,979 -- Counted cash flow rate of return: 44% discounted at 10% -- Payout period: 3.5 years, undiscounted -- Break-even selling price for 500g: Php 2.00 -- Break-even selling price for 120g pack: Php 1.25 -- Break-even capacity: 1365 kgs/month
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design
Keywords: Factories -- Design and construction; Agricultural processing plants; Yam industry